2010
DOI: 10.1590/s0101-20612010005000014
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of lipid microparticles produced by spray cooling encapsulating a low molar mass hydrophilic compound

Abstract: The objective of this research was to produce and characterize lipid particles (MpLs) that may be used as carriers of high amounts of hydrophilic core and evaluate the influence of the core amount on the performance of lipid microparticles. The MpLs were produced by spray cooling from solid and liquid lipid mixtures (stearic and oleic fatty acids and partly hydrogenated vegetable fat) containing glucose solution as core and soy lecithin as surfactant. The performance of MpLs was evaluated by means of the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
23

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 22 publications
1
8
0
23
Order By: Relevance
“…The mean diameters varied between 13.8 and 32.2 µm, and were thus within the range reported by the literature (SAVOLAINEN et al, 2002;LEONEL et al, 2010;CHAMBI et al, 2008).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The mean diameters varied between 13.8 and 32.2 µm, and were thus within the range reported by the literature (SAVOLAINEN et al, 2002;LEONEL et al, 2010;CHAMBI et al, 2008).…”
Section: Resultssupporting
confidence: 87%
“…Such variation in diameters can also be observed in the size distribution shown in Figure 5. Chambi et al (2008), Leonel et al (2010) and Ribeiro, Barrera-Arellano and Grosso (2012) found similar appearance of lipid microparticles encapsulating proteins and sugars as active substances. that softer matrices tend to produce larger microparticles.…”
Section: Surface Morphologymentioning
confidence: 73%
See 1 more Smart Citation
“…Several studies have been developed using the SC technique for the controlled release of drugs and cosmetics and the microencapsulation of proteins , hydrophilic and hydrophobic compounds , probiotics , and crystallization agents .…”
Section: Introductionmentioning
confidence: 99%
“…Tanto é que na literatura constam relatos da obtenção de micropartículas com tamanho médio na faixa de 13-50 µm (SAVOLAINEN et al, 2002;CHAMBI et al, 2008;LEONEL et al, 2010;RIBEIRO;ARELLANO;GROSSO, 2012;ALVIM et al, 2013) e 50-300 µm (RODRIGUEZ et al, 1999;MASCHKE et al, 2007;ALBERTINI et al, 2008;ILIĆ et al, 2009). Os valores de tamanhos médios de partícula obtidos nesse trabalho estão na faixa do que é citado na literatura como satisfatório para micropartículas produzidas por spray chilling.…”
Section: Análise Morfológica Das Mlsunclassified